Sistema automático de irrigação com água da chuva - Furtado, Lucas Jorhan Nishimura (2021)
This work consists of the study of an automated irrigation system for houseplants in order to guarantee the efficient use of rainwater. The system uses information from the soil moisture sensor to control the irrigation process. The system interface allows the visualization of the state that meets the level of the tanks. After the analyzes made by means of simulation, satisfactory results were found both for the reduction of the u se of drinking water and for the autonomous decision of the functioning of the process.